(untitled) (LEARNing Landscapes, 2024)
This work is an Indigenous Métissage weaving together poems, stories, scholarship, and images. It suggests that the distress, educational struggles, changes in traditional educational pathways, and other behaviors of current youth in response to social challenges offer ways out of these crises rather than being symptoms of them. This work offers pathways to learn from the wisdom of distress, and ways to create healing futures for ourselves, the land, waters, ancestors, and All Our Relations.